2016
DOI: 10.21608/ejvs.2016.1081
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms of GnRHR Gene and Its Relationship with Reproductive Performance in Egyptian Buffaloes

Abstract: HIS WORK aimed to search for single nucleotide polymorphisms of gonadotropin releasing hormone receptor (GnRHR) gene in Egyptian buffalo which involved in endocrine control of fertility. An ultrasonographic examinations of anestrum and repeat breeders' buffaloes were performed prior to blood sampling through a transrectal ultrasonography. DNA was extracted from blood and the PCR and singlestrand conformation polymorphism (SSCP) techniques were adopted to study of GnRHR gene polymorphism. The PCR amplified a fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Though has not been studied yet in sheep, GnRHR gene polymorphism has been proven efficiency in association with reproductive performance in several breeds of goats, such as Chinese goats (An et al, 2009), Boer goats (Yang et al, 2011), Loashan dairy goats (Liu et al, 2014), and Shaanan goats (Li et al, 2011). Furthermore, high genetic variation of GnRHR has also been reported in both Holstein Friesian cattle and Malnad Gidda buffalos (Kerekoppa et al, 2015), and in Egyptian buffalos (Sosa et al, 2016). However, no previous study was conducted to describe the possible association of the GnRHR with growth traits of sheep to compare our results with.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though has not been studied yet in sheep, GnRHR gene polymorphism has been proven efficiency in association with reproductive performance in several breeds of goats, such as Chinese goats (An et al, 2009), Boer goats (Yang et al, 2011), Loashan dairy goats (Liu et al, 2014), and Shaanan goats (Li et al, 2011). Furthermore, high genetic variation of GnRHR has also been reported in both Holstein Friesian cattle and Malnad Gidda buffalos (Kerekoppa et al, 2015), and in Egyptian buffalos (Sosa et al, 2016). However, no previous study was conducted to describe the possible association of the GnRHR with growth traits of sheep to compare our results with.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are accumulated pieces of evidence have increasingly been concerned with the importance of the GnRHR protein to act as a key element in the normal development of puberty (Zhang et al, 2018). Most mutations in GnRHR that either activate or inactivate their functions were reported to be responsible for several reproductive traits in domestic animals, such as cattle (Kerekoppa et al, 2015), buffalos (Sosa et al, 2016), and goats (Bemji et al, 2018). Thus, the investigation of single nucleotide polymorphisms (SNP) within this gene may be important to understand the possible causative SNP(s) behind a particular phenotypic trait.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the presence of mutation in poor semen quality bulls may suggest it responsibility in lower motility. Interestingly, Sosa et al (17) reported three nucleotide substitutions in GnRHR gene associated with ovarian inactivity in Egyptian buffaloes. So the genetic variation is needed for buffalo selection (34).…”
Section: Discussionmentioning
confidence: 99%
“…The primer for amplification of 240-bp fragments of GnRHR gene was described by Milazzotto et al (16) then Sosa et al (17) with the following nucleotide sequence: F: AAACTACAACTGAATCAGTC and R: TAGAGAGAAATATCCATATA. Amplification reactions were done in 50 l volume, containing 5.00 µl buffer 10x, 1.00 µl 2.5 mM (dNTPs mixture), 0.30 µl Taq polymerase (5 U/µl), 0.25µl primer, 3.00 µl 25 mM (MgCL2), 35.20µl water (nuclease free water) and 5.00 µl DNA sample.…”
Section: Pcr Reaction and Dna Amplificationmentioning
confidence: 99%
“…Several studies reported that this locus (bFSHR/ AluI) gene was associated with first ovulation post partum (Shirasuna et al 2011) and number inseminations per pregnancy (Arslan et al 2017). Therefore, the polymorphism of bFSHR/AluI gene was occured in indigenous Turkish cattle (Arslan et al 2015), European-Zebu composite (Marson et al 2008), Holstein cattle (Shirasuna et al 2011), Sudanese cattle (Omer et al 2016) and buffalo (Sosa et al 2015).…”
mentioning
confidence: 99%